Growth of Nitrosomonas and Nitrobacter in Sandy Soils Amended with Organic Constituents. - SALEH, S. M.; AZZOUZ, A. (The Libyan Journal of Agriculture, 2023)
Growth of Nitrosomonas in incubated soil samples amended with 170 ppm ammonium sulfate-N had apparently not been affected by dextrose incorporation. When an equivalent amount of nitrogen was applied as urea instead of ammonium sulfate, a tenfold suppression in growth was observed. A drastic effect for casein treatment was noted in both cases. Hence, counts slightly above 200 cells per gram soil were obtained after 2 days of incubation. Casein incorporation had apparently activated proteolytic groups of microorganisms whose synergistic effects were most pronounced by the alkaline soil condition imposed by substrate decomposition. Although Nitrobacter growth in ammonium sulfate-treated soils was not affected by dextrose incorporation, a significant growth appreciation was observed in urea-treated soils. Thus, counts of more than 1 x 10s were obtained within 14 days of incubation. The activity of urea hydrolyzing bacteria whose counts exceeded 1 x 10fi cells per gram soil in 4 days had apparently neutralized the synergistic effects ofother groups of heterotrophic bacteria. Therefore, the partial inhibition of Nitrobacter growth in casein-treated soils is likely to have occurred because of the sensitivity of this bacterium to the unfavorable soil pH prevailing after 2 days of incubation.